STATUS KESUBURAN TANAH GAMBUT PADA EMPAT TIPE PENGGUNAAN LAHAN DI DESA KUALA DUA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Joko, Joko; Vitri Indrawati, Urai Suci Yulies; Suryadi, Urai Edi (Fakultas Pertanian, Universitas Janabadra, 2024)
Raya Sub-district, Kubu Raya Regency on 4 lands namely Secondary Forest (HS), Shrubs (SB), Oil Palm (KS) and Pineapple (NS) which took place in April-June 2024. Research parameters: fill weight, peat maturity, peat depth, C-organic, CEC, KB, P-Total and K-Total. The data obtained was analyzed and then descriptive. The results showed that the depth of the peat was KS 5.05 m, HS 5.60 m, SB 6.25 and NS 6.10 m. The average pH (H2O) of the peat was highest in the soil. The average pH (H2O) of peat soil in the four land uses was 4.2 with very low criteria. The results of the peat maturity analysis with the average results on the four land uses have a hemic maturity category and have a P-total and K-total nutrient status of the soil classified as low, the CEC and C-organic status of the soil is very high and the base saturation level is very low so that the soil fertility status on the four lands is low. Keywords: soil physics, peat, fertility status